Synthesis and control of crosslinked poly(acrylic acid) based viscosity modifiers using dense phase carbon dioxide as a solvent - Alexander, W.H.; Wickson, J.; Duncan, J.; Carmichael, K.; Irvine, D.J.; Howdle, S.M. (Elsevier, 2018)
We investigate the clean synthesis of a cross-linked poly(acrylic acid) viscosity modifier using supercritical CO2 to replace more hazardous volatile organic solvents that are typically used for this process. The polymers were analysed by aqueous swell ratio studies to demonstrate the effect of process conditions such as pressure and temperature on the cross-link density of the materials. The reactions were optimised to yield high swelling polymers of up to 134 g water/g polymer. Dynamic mechanical analysis (DMA) was also applied to investigate the mechanical properties of the synthesised cross-linked poly(acrylic acid) materials and these data were directly correlated with swell ratio. In addition, rheological studies demonstrate that the hydrated gels are comparable with commercially available equivalents.